If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4-2x+6x=8
We simplify the equation to the form, which is simple to understand
-4-2x+6x=8
We move all terms containing x to the left and all other terms to the right.
-2x+6x=+8+4
We simplify left and right side of the equation.
+4x=+12
We divide both sides of the equation by 4 to get x.
x=3
| 2(c+4)=14+c | | 4.7x+2.4=16.5 | | 4(10+6x)=184 | | 0.11y+1.5=2.49 | | i/7=-9 | | ((6x-5)^2+8)/3^2=0 | | 15/27=50/x | | g^2-12g+6=-21 | | 0.5c-1.9=2.8+0.6c | | x+109=89+x | | 2x^2+1=-35 | | 5/11(11x+7)=0 | | 2x-7=3(x+1)-5 | | 4-10a=3+4a | | -5=-2x+x+5 | | 2*(5x+1)=7x-4 | | n-4/-3=4 | | n^2-11n+3=5 | | 13=-5x+3x+3 | | 13.25=0.5y+8.75 | | 3(2+4)=7x-5 | | 2+2(4n-1)=56 | | 2x-40+(x-10)=180 | | ((6x-5)^2+8)/3^2 | | 3z-12=57 | | 42=x+7x+10 | | 23676x(2+8)=2 | | 2xy^2(3x+2y+4)= | | 2+2=2+2*2 | | 6/15=25/x | | 2b-2=12 | | 6x+2+7x=80 |